Affirmative action and application strategies: Evidence from field experiments in Columbia - Ritwik Banerjee; Marcela Ibanez; Gerhard Riener; Soham Sahoo (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
Affirmative action changes incentives at all stages of the employment process. In this paper, we study the effects of affirmative action statements in job ads on i) the effort expended on the application process and ii) the manifestation of emotions, as measured by the textual analysis of the content of the motivation letter. To this end, we use data from two field experiments conducted in Colombia. We find that in the Control condition, women spend less time in the application process relative to men. Besides, female motivation letters exhibit lower levels of emotion, as measured by valence, arousal, and dominance. However, those differences vanish in the affirmative action treatment when we announced to job-seekers that half of the positions were reserved for women. In the Affirmative Action condition, the time dedicated by women significantly increased and the motivation letters written by the female candidates showed a significant increase in the expression of positive emotions. The results indicate that affirmative action policies can have significant encouraging effects on both effort and appeal of job applications of women, thereby reducing the gender gap in these outcomes.
Keywords: C91; J15; M52; 330; Gender; Labor economics; Field experiment